2018
DOI: 10.1111/andr.12524
|View full text |Cite
|
Sign up to set email alerts
|

A‐kinase anchor protein 4 precursor (pro‐AKAP4) in human spermatozoa

Abstract: This study generated new knowledge about pro-AKAP4 in human semen, which may be of interest in the management of male infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 19 publications
7
27
0
Order By: Relevance
“…By contrast, and in agreement with our own data, proAKAP4 is retained within the flagellum of mature human spermatozoa, where it co-localizes with AKAP4 throughout the fibrous sheath (Turner et al, 1998;Jumeau et al, 2018). Notably however, striking differences in proAKAP4 abundance have been documented in the semen of normozoospermic individuals, wherein the quantity of the protein is positively correlated with sperm motility; albeit in the high-quality cells recovered by density gradient centrifugation (Jumeau et al, 2018). Whilst these data invite speculation that the extent of proAKAP4 processing may reflect the integrity of post-testicular sperm maturation, and hence contribute to differences in the motility profile of human spermatozoa, there is currently no causal evidence to substantiate such an association.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…By contrast, and in agreement with our own data, proAKAP4 is retained within the flagellum of mature human spermatozoa, where it co-localizes with AKAP4 throughout the fibrous sheath (Turner et al, 1998;Jumeau et al, 2018). Notably however, striking differences in proAKAP4 abundance have been documented in the semen of normozoospermic individuals, wherein the quantity of the protein is positively correlated with sperm motility; albeit in the high-quality cells recovered by density gradient centrifugation (Jumeau et al, 2018). Whilst these data invite speculation that the extent of proAKAP4 processing may reflect the integrity of post-testicular sperm maturation, and hence contribute to differences in the motility profile of human spermatozoa, there is currently no causal evidence to substantiate such an association.…”
Section: Discussionsupporting
confidence: 92%
“…proAKAP4 has been reported to localize along the entire length of the principal piece of mouse testicular spermatozoa before becoming restricted to the proximal portion of the flagellum in mature cauda epididymal spermatozoa (Johnson et al, 1997); suggestive of an additional wave of proAKAP4 processing during epididymal sperm maturation. By contrast, and in agreement with our own data, proAKAP4 is retained within the flagellum of mature human spermatozoa, where it co-localizes with AKAP4 throughout the fibrous sheath (Turner et al, 1998;Jumeau et al, 2018). Notably however, striking differences in proAKAP4 abundance have been documented in the semen of normozoospermic individuals, wherein the quantity of the protein is positively correlated with sperm motility; albeit in the high-quality cells recovered by density gradient centrifugation (Jumeau et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Previous investigation identified that AKAP4 is a member of the AKAP family, which constitutes a conserved family of signal‐organising scaffolding proteins involved in a series of cellular processes, especially in human spermatogenesis (Jumeau et al., 2018; Luconi et al., 2011). A genome‐wide survey identified AKAP4 as the testis‐restricted cancer‐testis antigen (CTA) (Hofmann et al., 2008).…”
Section: Discussionmentioning
confidence: 99%